Reaksi Pasar Modal Terkait Penyuntikan Vaksin COVID 19 Pertama Indonesia pada Perusahaan Sektor Farmasi di Bursa Efek Indonesia - Ni Komang Sri Purnami; Sunitha Devi (Universitas Pendidikan Ganesha, 2022)
The purpose of this study is to establish whether or not there is a stock market reaction using variables of abnormal return, trading volume activity, and bid ask spread before and after injection of the first COVID 19 vaccine in Indonesia. This type of study is an event study. The population of this study is pharmaceutical sector companies listed in Indonesia Stock Exchange. Sampling technique used sampling total method with number 20 companies. Data analysis that used are descriptive statistical analysis, normality test, and hypothetical test (paired sampel t-test) with the observation period of 14 working days on the stock exchange. The result of this study indicated that: (1) There was average difference in the abnormal return before and after injection of the first COVID 19 vaccine in Indonesia; (2) There was average difference in trading volume activity before and after injection of the first COVID 19 vaccine in Indonesia; (3) There was average difference on bid ask spread before and after injection of the first COVID 19 vaccine in Indonesia.